Teaching higher education courses in Further Education colleges - Tummons, Jonathan; Orr, Kevin; Atkins, Liz (SAGE Publications, Ltd, 2013)
As the number of higher education (HE) courses offered in further education (FE) settings increases, so does the need for teachers and trainee teachers to develop their teaching skills. This text is written for all those working towards QTLS who are teaching or planning to teach HE courses. It examines what it means to teach HE and how a HE environment can be created in an FE setting. It gives guidance on planning, teaching and assessing HE courses in FE. A practical guide for all FE teachers and trainee teachers as the sector adapts to the needs of education today